Expectant Management of Monochorionic-Triamniotic Triplets Complicated by Selective In Utero Growth Restriction: Report of 2 Cases - Laurence Carmant; Sandrine Wavrant; Elisabeth Codsi (Hindawi Limited, 2020)
The optimal management of monochorionic-triamniotic (MCTA) triplet pregnancies is not clearly established, and there is no literature to guide management of MCTA complicated with selective intrauterine growth restriction (sIUGR). This gap in knowledge and the concern for higher risk of severe complications have led some medical societies to recommend selective termination of nontrichorionic triplet pregnancies. We sought to report the favourable outcomes of two MCTA complicated by sIUGR expectantly managed at Sainte-Justine Hospital, Montreal, Canada. The first case is of a 42-year-old woman with spontaneous MCTA triplets diagnosed at 18 weeks with type II sIUGR who opted for expectant management. The second patient was a 22-year-old woman with a spontaneous MCTA triplet pregnancy diagnosed at 18 weeks with type III sIUGR. Our experience shows that close serial ultrasounds could potentially allow physicians to foresee fetal deterioration. In our opinion, expectant management should be considered as a management option for MCTA complicated by sIUGR.